2019
DOI: 10.3390/jcm8071063
|View full text |Cite
|
Sign up to set email alerts
|

Best Evidence Rehabilitation for Chronic Pain Part 3: Low Back Pain

Abstract: Chronic Low Back Pain (CLBP) is a major and highly prevalent health problem. Given the high number of papers available, clinicians might be overwhelmed by the evidence on CLBP management. Taking into account the scale and costs of CLBP, it is imperative that healthcare professionals have access to up-to-date, evidence-based information to assist them in treatment decision-making. Therefore, this paper provides a state-of-the-art overview of the best evidence non-invasive rehabilitation for CLBP. Taking togethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
82
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 111 publications
2
82
0
7
Order By: Relevance
“…It is worth highlighting that small effect sizes were obtained in the group of subjects who received the usual physiotherapy treatment. However, as other studies have shown, the existence of CS predicts poor outcomes obtained with classic local treatments, such as electrotherapy, motor control exercises, and surgery [107,108]. Sometimes PE can increase symptoms because descending inhibitory systems are not working properly [83], and some authors even point out that exercise can induce hyperalgesia if psychosocial factors such as fear of pain, catastrophism, and erroneous beliefs are not previously addressed, and this was not done in the CG [109].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth highlighting that small effect sizes were obtained in the group of subjects who received the usual physiotherapy treatment. However, as other studies have shown, the existence of CS predicts poor outcomes obtained with classic local treatments, such as electrotherapy, motor control exercises, and surgery [107,108]. Sometimes PE can increase symptoms because descending inhibitory systems are not working properly [83], and some authors even point out that exercise can induce hyperalgesia if psychosocial factors such as fear of pain, catastrophism, and erroneous beliefs are not previously addressed, and this was not done in the CG [109].…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiment and mathematical model of the spine indicated that sequential injuries and deep muscles weakness resulted in spinal instability [2], which is defined as a significant decrease in the capacity of the spinal stabilizing system to maintain the intervertebral neutral zone within physiological limits [3]. Clinical guidelines suggested that spinal stabilization exercises (SSEs) may be as effective as other physiotherapy treatments in reducing disability and pain [4,5]. The principle of SSEs is to train the cocontraction pattern of the deep local trunk muscles of the transversus abdominis (TA) and the multifidus muscles (MF).…”
Section: Introductionmentioning
confidence: 99%
“…As the name suggests, FR puts emphasis on restoring body functions instead of simply reducing the pain, which used to be the dominant focus for recovery with regard to CLBP before FR was introduced. Since its introduction, systematic reviews have presented evidence that applying multidisciplinary biopsychosocial rehabilitation (MBR), which follows the principles of FR leads to reduced pain, quicker return to work or improved functions when compared to usual care or nonmultidisciplinary rehabilitation approaches [3,[5][6][7]. However, these findings were not uniformly confirmed [8][9][10].…”
Section: Introductionmentioning
confidence: 99%